Evaluation of Hepatoprotective and Nephroprotective Impact of Phytomedicine using Experimental Animal Models - Muhammad Jahangeer; Humayun Ameen; Ghazia Fatema; Muti Ur Rehman; Shaista Nawaz; Kashaf Tariq; Shamma Firdous; Shafqat Munir; Muhammad Hassan Farooq; Afifa Maryam; Areej Riasat (International Health Review, 2024)
Human beings have been using plants as medicines for centuries. The development of traditional medicinal systems utilizing plants as a form of medicine may be traced back only as far as historical documentation of their similarity. Immunosuppression and bone resorption is a major drawback in conventional chemotherapy. Modern medicines contain plant-derived components that are the source of immunomodulators. Withania somnifera and Cnidium monnieri are the plants which have been used for immunomodulatory and anti-osteoporotic activities. Medicinal plant samples were obtained from diverse parts of Pakistan. Following extraction, phytochemical analysis and antimicrobial potential were investigated, and the hepatoprotective effect was evaluated. An in vivo study was conducted on experimental animals by administering ethnomedicinal plant extracts in comparison to some allopathic drugs. Various blood samples were collected to analyze calcium level, vitamin-D, thyroid-stimulating hormone (TSH), parathyroid hormone (PTH), follicle stimulating hormone (FSH), and Testosterone for antiosteoporosis activity. The possible outcomes were positive and hepatoprotective as well as antimicrobial effect was present in Polyherbal preparation (PHP). During trails on Albino rats, the improvement in their body weight was recorded. PHP administration of plant extracts enhanced the parameters of blood and neutralized the effect of CCl4 intoxication. The proper administration of plant extracts showed a positive effect on hormones, particularly progesterone, testosterone, and oestradiol. In the future, these selected medicinal plants and their PHP might be preferred for the separation of lead bioactive compounds to overcome the extremely alleviating issues associated with infertility.